The Role of Emotions in Classroom Conflict Management. Case Studies Geared Towards Improving Teacher Training - Alvarez, Ibis M.; González-Parera, Montserrat; Manero, Borja (Frontiers in Psychology, 2022)
The purpose of this paper is twofold: firstly, to explore the emotional aspects underlying classroom conflict management, and secondly, to apply these notions to the contrasted analysis of two case studies. Our findings underscore the importance of examining teachers’ emotional regulation to better understand their performance when dealing with conflicts that affect classroom climate. In the final section, we make suggestions for introducing this perspective into initial teacher training through the use of Virtual Reality, a scenario that would allow pre-service teachers to experiment, record and reflect on affective and attitudinal issues that are decisive for effective classroom conflict management.